3D printed circular nodal plate stacks for broadband vibration isolation. (23rd June 2023) - Rai, George; Rahn, Christopher; Smith, Edward; Marr, Conor
Abstract: This paper introduces additively manufactured plate stack isolators capable of broadband vibration isolation over multiple frequency ranges. The isolator consists of axisymmetric stepped plates stacked in series and connected using compliant hinges. The monolithic design eliminates friction, leading to deeper stop bands and a potentially larger cycle life. A Kirchhoff–Love plate model predicts the frequency response. Additively manufactured polymer plate network isolators show that multiple band gaps can be achieved by model based tuning of plate geometries. A sensitivity study shows that additive manufacturing tolerance errors affect the width and center frequency of the band gap. Finally, the experimentally validated model predicts that metal isolators manufactured with Laser Powder-Bed fusion are capable of achieving low frequency band gaps and other design metrics of commercially available vibration isolators.